Thromboembolic risk stratification by TRiP(cast) score to rationalise thromboprophylaxis in patients with lower leg trauma requiring immobilisation: a study protocol of the casting stepped-wedge cluster randomised trial. Issue 6 (28th June 2021) - Douillet, Delphine; Riou, Jeremie; Thoma, Maximilien; Moumneh, Thomas; Darsonval, Astrid; Trinh-Duc, Albert; Hugli, Olivier; Chauvin, Anthony; Penaloza, Andrea; Roy, Pierre-Marie
Abstract : Introduction: Patients with lower limb trauma requiring orthopaedic immobilisation may be at risk of venous thromboembolism but opinions differ about who may benefit from thromboprophylactic anticoagulant treatment. The aim of this CASTING study is to demonstrate the safety of thromboprophylaxis based on the Thrombosis Risk Prediction for patients with cast immobilisation (TRiP(cast) score with regards to the 3-month incidence of symptomatic venous thromboembolism events in low-risk patients not receiving thromboprophylaxis, as well as the usefulness of this strategy on the rate of patients receiving anticoagulant treatment in comparison to current practice. Methods and analysis: CASTING will be a stepped-wedge cluster randomised controlled clinical trial, performed in 15 emergency departments in France and Belgium. With their informed consent, outpatients admitted to one of the participating emergency departments for a lower limb trauma requiring orthopaedic immobilisation without surgery will be included. All centres will begin the trial with the 'observational period' and, every 2 weeks, 1 centre will be randomly assigned to switch to the 'interventional period' and to apply the TRiP(cast) score, in which only patients with a score ≥7 will receive thromboprophylactic anticoagulant treatment. The primary endpoint is the rate of clinical thromboembolic events within 90 days following the inclusion of low-risk patients not receiving thromboprophylaxis. Ethics and dissemination: The protocol has been approved by the Comité de Protection des Personnes Sud I (Ethics Review ID-RCB: 2019-A01829-48) for France and the Comité d'éthique hôpital-facultaire Saint Luc (N° B403201941338) for Belgium. It is carried out in accordance with the Declaration of Helsinki and Good Clinical Practice guidelines. The findings of this study will be disseminated in peer-reviewed journals and at scientific conferences. Trial registration number: NCT04064489 .